1999
DOI: 10.1159/000020908
|View full text |Cite
|
Sign up to set email alerts
|

Can We Suspect Fetal Down Syndrome by Heart Evaluation during the Second Half of Pregnancy?

Abstract: Thirty fetuses with Down syndrome, who had detailed fetal echocardiography and sonography at the tertiary center with videotape recordings, were retrospective analyzed by one observer with a specially prepared flow sheet. The mean gestational age of the fetuses at the time of the study was 31 ± 5.6 (minimum 21, maximum 39) weeks. The ‘main’ fetal abnormalities were congenital heart defect (CHD): in 13 cases (43.3%) an abnormal 4-chamber view was recorded, including 6 cases (20%) of isolated CHD and 7 (23.3%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Overall, CHDs complicate approximately 0.8–1% of live births (Hoffman & Kaplan, 2002); however, postnatal studies have reported that approximately half of all newborns with T21 are diagnosed with CHD (Bergström et al, 2016; Freeman et al, 2008; Kallen et al, 1996; Morris et al, 2014; Santoro et al, 2018; Stoll et al, 1998; Stoll et al, 2015; Torfs & Christianson, 1998). Nonetheless, prenatal studies have reported various rates of CHD prevalence (Hyett et al, 1995; Mogra et al, 2011; Morris et al, 2014; Paladini et al, 2000; Respondek‐Liberska et al, 1999), but most have only included small numbers of patients with DS (Table 1). Moreover, a recent study has highlighted a phenotypic shift in the spectrum of CHDs, noting that fewer children are born with T21 and complex anatomical defects such as AVSD, presumably due to improvements in the prenatal diagnosis of CHDs and an increase in selective abortions in complex CHD cases (Bergström et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, CHDs complicate approximately 0.8–1% of live births (Hoffman & Kaplan, 2002); however, postnatal studies have reported that approximately half of all newborns with T21 are diagnosed with CHD (Bergström et al, 2016; Freeman et al, 2008; Kallen et al, 1996; Morris et al, 2014; Santoro et al, 2018; Stoll et al, 1998; Stoll et al, 2015; Torfs & Christianson, 1998). Nonetheless, prenatal studies have reported various rates of CHD prevalence (Hyett et al, 1995; Mogra et al, 2011; Morris et al, 2014; Paladini et al, 2000; Respondek‐Liberska et al, 1999), but most have only included small numbers of patients with DS (Table 1). Moreover, a recent study has highlighted a phenotypic shift in the spectrum of CHDs, noting that fewer children are born with T21 and complex anatomical defects such as AVSD, presumably due to improvements in the prenatal diagnosis of CHDs and an increase in selective abortions in complex CHD cases (Bergström et al, 2016).…”
Section: Introductionmentioning
confidence: 99%